The effect of surgeon experience and insertion speed on intracochlear pressures during in-vitro cochlear implantation - Crohan, William; Tavora-Vieira, Dayse; Voola, Marcus; Acharya, Aanand; Rajan, Gunesh P. (Frontiers in Audiology and Otology, 2024)
Hypothesis That increased insertion speed is associated with increased intracochlear pressure variation. Background Preservation of residual hearing is an important goal of modern cochlear implant surgery. Many factors, including intracochlear pressure changes during insertion, are thought to be significant in the preservation of residual hearing through the reduction in intraoperative trauma to the cochlea. Methods Participants at a cochlear implantation hearing preservation workshop open to surgeons and audiologists were invited to participate in a challenge to insert a cochlear implant electrode into an in-vitro model of a cochlea. Intracochlear pressure variation was measured as a surrogate marker for intracochlear trauma against insertion speed, method of insertion, moisturization of the electrode, and participant experience. Results The study demonstrated that the relative experience of a surgeon and the speed of insertion were significant for maximal intracochlear pressure variation. The more experienced participants were likely to demonstrate lower pressure variation, and a slower insertion on average produced significantly smaller pressure changes than faster insertions. No other variables were deemed significant for maximal intracochlear pressure variation. Conclusion Surgeon experience and speed of implant insertions were significant factors in the reduction of intracochlear pressure variation during cochlear implantation simulations